SOME BIOLOGICAL INDICATORS OF TYPE 2 DIABETES OUTPATIENTS AT SOME GENERAL HOSPITALS OF NORTHERN VIETNAM IN 2020-2022 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe some biochemical indicators of patients with type 2 diabetes.Methods: A cross-sectional descriptive study was carried out on 1586 patients who suffered fromtype 2 diabetes have been undergoing treatment at the Outpatient Department of Ha Nam ProvincialGeneral Hospital; Huu Nghi Hospital; Bac Quang Binh General Hospital; Quang Ninh ProvincialGeneral Hospital in 2020-2022.Results: The proportion of patients with high blood triglycerides was 40.6%; this rate was lower inmale patients than in female patients; high blood LDL-C rate was 39.2%; also lower in men than inwomen. Other indicators for the whole study group were: the rate of high blood glucose: 67.4%; highHbA1c: 77.8%; and no difference between men and women has been found.
Keywords: Mellitus diabetes, biochemical index.